Implementation of Porter’s Generic Strategies in The UK Fashion Retail E-Commerce - Rafee, Raqibul Alam (Academic Journal on Business Administration, Innovation & Sustainability, 2024)
The application, and implementation of Porter’s Generic Strategies in the UK e-commerce fashion retail industry are the main topics of this study into the strategic management practices of UK e-commerce companies. The study will evaluate how major fashion retailers in the UK have adopted and implemented Porter’s strategies of cost leadership, differentiation and focus to gain competitive advantage in the market. Academics, practitioners, and business leaders looking to improve their competitive standing and make wise strategic decisions will benefit greatly from the findings.